Visual Outcome of Phacoemulsification Versus Small Incision Cataract Surgery: Doi: 10.36351/pjo.v37i1.1140 - Das, Narain; Shaikh, Asma Shams; Kumar, Jai; Khan, Beenish; Bhatti, Nasir (Pakistan Journal of Ophthalmology, 2020)
Purpose: To determine visual rehabilitation of Phacoemulsification in comparison to small incision cataract surgery after implantation of rigid intraocular lens. Study Design: Quasi Experimental Study. Place and Duration of Study: Shaheed Mohtarma Benazir Bhutto Medical College Lyari and Sindh Government Lyari General Hospital, Karachi, from July 2018 to December 2019. Methods: Patients with 35 – 70 years age and diagnosed with senile cataracts and visual acuity of <6/36were included. Patients having any corneal disease, intra-ocular pressure > 22 mmHg, high ametropia, any other eye disease were excluded. Patients were divided into two groups of 80 patients each. Group I underwent Phaco-emulsification and group II had Small incision cataract surgery. For data analysis, SPSS version 20.0 was used. Frequency and percentages were calculated for qualitative data and quantitative data was presented as mean and standard deviation. Results: In a total of 160 patients operated of cataract, male to female ratio was 1:1. The range of astigmatism after 6 months in the group I was between 0.5 – 1.00 D while in the group II, it was between 0.75 – 1.75 D. Uncorrected visual acuity and best corrected visual acuity of 6/18 or better was seen in 90 and 97% group 1 while it was 85% and 95% in group II patients respectively at sixth month. Conclusion: No significant difference was seen in uncorrected and best corrected visual acuity between the two groups. Time of surgery was lesser group 2 and Astigmatism was lesser in group 1. Key Words: Phaco-emulsification, Small Incision Cataract Surgery, Visual Rehabilitation.